CORONA DISCHARGE AS ONE OF THE FACTORS OF DECREASE OF FIBER-OPTICAL COMMUNICATION LINES LIFE - Igor A. Semko; Vladimir A. Osipov; Georgy E. Solovyev (Advanced Engineering Research)
The research results of the electrothermic degradation of fiber-optical communication lines caused by the external electromagnetic fields impact are offered.